Højrup, Thomas & Klaus Bolving (red.): Velfærdssamfund – velfærdsstaters forsvarsform? - Mik-Meyer, Nanna; Petersen, Karen Lund (Tidsskriftet Antropologi, 2007)
Anmeldes af Nanna Mik-Meyer & Karen Lund Petersen